2012
DOI: 10.4103/0970-0218.94019
|View full text |Cite
|
Sign up to set email alerts
|

A time motion study in the immunization clinic of a tertiary care hospital of Kolkata, West Bengal

Abstract: Background:A time and motion study is used to determine the amount of time required for a specific activity, work function, or mechanical process. Few such studies have been reported in the outpatient department of institutions, and such studies based exclusively on immunization clinic of an institute is a rarity.Materials and Methods:This was an observational cross sectional study done in the immunization clinic of R.G. Kar Medical College, Kolkata, over a period of 1 month (September 2010). The study populat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
14
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 1 publication
1
14
0
Order By: Relevance
“…This may be due to healthcare workers taking more time to enter various sociodemographic details during initial registration. These results were similar to a study conducted in Kolkata which also shows maximum time (46.3%) at the immunization clinic were spent in getting postvaccination advice [ 8 ].…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…This may be due to healthcare workers taking more time to enter various sociodemographic details during initial registration. These results were similar to a study conducted in Kolkata which also shows maximum time (46.3%) at the immunization clinic were spent in getting postvaccination advice [ 8 ].…”
Section: Discussionsupporting
confidence: 89%
“…Many studies have found that long waiting times and insufficient and inefficient staff as major obstacles faced by healthcare facilities in developing countries [ 8 ]. In the present study, it was observed that study participants had to spend 64.1% of their time at the immunization clinic in waiting to get service from immunization clinic.…”
Section: Discussionmentioning
confidence: 99%
“…A time and motion study (or time-motion study) is a business efficiency technique combining the time study work of Frederick Winslow Taylor (1881 A.D) with the motion study work of Frank B. Gilberth and his wife Lillian Gilbreth (1885A.D). It is a major part of scientific management (Taylorism) 1 . Motion study is designed to determine best way to complete a repetitive job while the time study measures how long it takes an average worker to complete a task at a normal pace.…”
Section: Introductionmentioning
confidence: 99%
“…We have discussed the time-motion article( 1 ) under articles review session and we would like to discuss our observations.…”
mentioning
confidence: 99%
“…( 2 ) Taking cognizance of present trends and recognizing the fact that motion study always precedes the setting of a time standard, was presented in the same article. ( 1 )…”
mentioning
confidence: 99%